2002
DOI: 10.1128/jvi.76.11.5769-5783.2002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction between the pp71 Protein of Human Cytomegalovirus and the PML-Interacting Protein Human Daxx

Abstract: The tegument protein pp71 (UL82) of human cytomegalovirus (HCMV) has previously been shown to transactivate the major immediate-early enhancer-promoter of HCMV. Furthermore, this protein is able to enhance the infectivity of viral DNA and to accelerate the infection cycle, suggesting an important regulatory function during viral replication. To gain insight into the underlying mechanisms that are used by pp71 to exert these pleiotropic effects, we sought for cellular factors interacting with pp71 in a yeast tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
183
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(201 citation statements)
references
References 72 publications
(99 reference statements)
14
183
3
1
Order By: Relevance
“…Upon infection, tegument pp71 translocates to the nucleus and facilitates the degradation of nuclear Daxx, thereby relieving suppression of the MIEP and promoting viral replication (41). In agreement with other studies (13,34,38), we observed a ∼5-fold induction of the MIEP by pp71 in fibroblasts (Fig. 6).…”
Section: Discussionsupporting
confidence: 81%
“…Upon infection, tegument pp71 translocates to the nucleus and facilitates the degradation of nuclear Daxx, thereby relieving suppression of the MIEP and promoting viral replication (41). In agreement with other studies (13,34,38), we observed a ∼5-fold induction of the MIEP by pp71 in fibroblasts (Fig. 6).…”
Section: Discussionsupporting
confidence: 81%
“…It is supported by the facts that SUMO-1 molecules aggregate in ND10 and ND10 might be the hot sites for SUMOylation, that the acetylation and phosphorylation of p53 at PML bodies enhance the activity of p53 [16,81,82] , and that the 19S and 20S proteasome subunits localize at some PML bodies [83] .…”
Section: Hotspot Modelmentioning
confidence: 60%
“…The first ND10 protein investigated for its role in HCMV gene expression and viral replication was Daxx. In that study, Daxx was found to interact functionally with HCMV tegument protein pp71 [16] . The Stamminger group [99] also investigated PML to see whether PML could have any effects on viral gene expression or on viral replication.…”
Section: Cytomegalovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional evidence demonstrated that pp71 induced the degradation of Daxx [2,4] through an unusual proteasome dependent, ubiquitin independent manner [38], but did not disrupt PML-NBs [2]. However, pp71-mediated Daxx degradation induces the expression of the viral IE1 protein [2,[39][40][41][42], and IE1 subsequently disrupts PML-NBs by altering the SUMOylation state of PML [27,43,44] and perhaps other proteins as well. As stated above, the fact that these herpesviral proteins degraded and disrupted PML-NBs implied, but did not demonstrate, that PML-NB proteins antagonize herpesviral infections.…”
Section: Several Proteins That Localize To Pml-nbs Repress the Transcmentioning
confidence: 99%